The Basic Leucine Zipper Domain Transcription Factor Atf1 Directly Controls Cdc13 Expression and Regulates Mitotic Entry Independently of Wee1 and Cdc25 in Schizosaccharomyces pombe - Bandyopadhyay, Sushobhana (American Society for Microbiology, 2014)
Progression into mitosis is a major point of regulation in the Schizosaccharomyces pombe cell cycle, and its proper control is essential for maintenance of genomic stability. Investigation of the G(2)/M progression event in S. pombe has revealed the existence of a complex regulatory process that is responsible for making the decision to enter mitosis. Newer aspects of this regulation are still being revealed. In this paper, we report the discovery of a novel mode of regulation of G(2)/M progression in S. pombe. We show that the mitogen-activated protein kinase (MAPK)-regulated transcription factor Atf1 is a regulator of Cdc13 (mitotic cyclin) transcription and is therefore a prominent player in the regulation of mitosis in S. pombe. We have used genetic approaches to study the effect of overexpression or deletion of Atf1 on the cell length and G(2)/M progression of S. pombe cells. Our results clearly show that Atf1 overexpression accelerates mitosis, leading to an accumulation of cells with shorter lengths. The previously known major regulators of entry into mitosis are the Cdc25 phosphatase and the Wee1 kinase, which modulate cyclin-dependent kinase (CDK) activity. The significantly striking aspect of our discovery is that Atf1-mediated G(2)/M progression is independent of both Cdc25 and Wee1. We have shown that Atf1 binds to the Cdc13 promoter, leading to activation of Cdc13 expression. This leads to enhanced nuclear localization of CDK Cdc2, thereby promoting the G(2)/M transition.